2020
DOI: 10.3390/su12104135
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Chinese Residents’ Waste Classification from a Perspective of Intention–Behavior Gap

Abstract: It remains uncertain as to whether people who support waste classification end up transforming such environmental initiation into reality. Thus, to investigate the intention and actual behavior of Chinese residents on waste classification and the influencing factors, this study integrated the theory of planned behavior (TPB) and norm activation model (NAM), and extended them by adding external information factors, namely information publicity type and information quality. A questionnaire survey was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 66 publications
(109 reference statements)
1
7
0
Order By: Relevance
“…The TPB was first presented by Ajzen (1991) , which has been used to predict pro-environmental intentions and behaviors in various research domains, including sustainable travel modes ( Donald et al, 2014 ), organic food consumption ( Canova et al, 2020 ), bicycle tourism ( Lin et al, 2020 ), and waste separation practicing ( Zhang et al, 2020a ). According to TPB, there are three reliable antecedents that lead to behavioral intention, namely attitudes (AT), subjective norms (SN), and perceived behavioral control (PBC).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The TPB was first presented by Ajzen (1991) , which has been used to predict pro-environmental intentions and behaviors in various research domains, including sustainable travel modes ( Donald et al, 2014 ), organic food consumption ( Canova et al, 2020 ), bicycle tourism ( Lin et al, 2020 ), and waste separation practicing ( Zhang et al, 2020a ). According to TPB, there are three reliable antecedents that lead to behavioral intention, namely attitudes (AT), subjective norms (SN), and perceived behavioral control (PBC).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In addition, few studies have explored the relationship between intention and behavior, because intention has been widely recognized as the main construct that leads to actual behavior in TPB. However, the declared intention is not identical variable to the actual behavior, and it has been found that an intention-behavior gap may exist in pro-environmental behaviors ( Zhang et al, 2020a ). In our previous work, it has been found that Hangzhou citizens are supportive of local public transport policies and have intention to reduce car use ( Zhang et al, 2020b ), but the problems caused by private cars are still far from being solved.…”
Section: Introductionmentioning
confidence: 99%
“…In the fourth stage, individuals have many beliefs related to behavior, and only a part of them can be acquired subjectively under a specific time and environment. These accessible beliefs are called salient beliefs, and all other factors must indirectly influence these salient beliefs [ 14 , 15 , 16 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies have shown that external environmental factors, such as information publicity [ 18 ], facility conditions [ 19 ] and information quality [ 20 ], place a significant impact on waste behavioral willingness. In addition to the essential external environmental factors, internal factors, which are less acknowledged by most researchers, are found to equally contribute to it.…”
Section: Literature Reviewmentioning
confidence: 99%